Drug interchangeability multi source in peru: the need to establish a technical directive - Meza, Katia L. (2013)
This descriptive and analytical work, aims to evaluate the need to implement a Technical Directive for studies that ensure interchangeability of multisource drugs in Peru, based on quality, efficacy and safety. It is suggested the interchangeability through compliance with Good Manufacturing Practices, quality specifications and therapeutic equivalence, as well as, a list of active ingredients that had proven to be interchangeable in vivo and in vitro studies. We conclude that regulation is needed to ensure the interchangeability of multisource drug, that permit update regulation systems according to international harmonization programs, ensure quality, efficacy and safety of this drug, reduce public health spending providing medicines universal access and generate greater confidence regarding the quality of our products.